2017
DOI: 10.1111/cge.13100
|View full text |Cite
|
Sign up to set email alerts
|

Novel non‐neutral mitochondrial DNA mutations found in childhood acute lymphoblastic leukemia

Abstract: Mitochondria produce adenosine triphosphate (ATP) for energy requirements via the mitochondrial oxidative phosphorylation (OXPHOS) system. One of the hallmarks of cancer is the energy shift toward glycolysis. Low OXPHOS activity and increased glycolysis are associated with aggressive types of cancer. Mitochondria have their own genome (mitochondrial DNA [mtDNA]) encoding for 13 essential subunits of the OXPHOS enzyme complexes. We studied mtDNA in childhood acute lymphoblastic leukemia (ALL) to detect potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
0
16
2
Order By: Relevance
“…Such tumor-exclusive variants were distributed in 13 genes, of which three (MT- ATP8 , MT- ND4L and MT- TG ) were only observed in this group. Only a few studies have reported variants in MT- ATP8 31,32 and MT- ND4L 31,3335 in different types of cancer and none was in gastric cancer. No studies were found associating variants in MT- TG to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Such tumor-exclusive variants were distributed in 13 genes, of which three (MT- ATP8 , MT- ND4L and MT- TG ) were only observed in this group. Only a few studies have reported variants in MT- ATP8 31,32 and MT- ND4L 31,3335 in different types of cancer and none was in gastric cancer. No studies were found associating variants in MT- TG to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In 8 out of 36 patients, missense or nonsense mutations in mtDNA (components of ETC-Complex I, Complex IV and the ATP synthase) were found, and 6 out these 8 patients died from ALL. Within the whole group, there was a correlation between a poor prognosis at diagnosis due to genetic markers and a mutated mtDNA pattern [31].…”
Section: Metabolic Hallmarks Of Pediatric Allmentioning
confidence: 91%
“…Such mtDNA mutations are also described in patients with cALL as shown by the detection of 73 nonneutral mutations in 36 patients 13,14 . The affected genes code for components of the ETC—Complex I (MT‐ND1, MT‐ND2, MT‐ND4L, and MT‐ND6), Complex IV (MT‐CO3), and the ATP synthase (MT‐ATP8) 14 . Even if functional data on these SNPs are not provided, such mutations are likely capable of altering the activity of the ETC.…”
Section: Cell Metabolism In Callmentioning
confidence: 95%
“…Mutations in mitochondrial DNA (mtDNA) genes encoding components of oxidative phosphorylation (OxPhos) are present in a number of malignancies 12 . Such mtDNA mutations are also described in patients with cALL as shown by the detection of 73 nonneutral mutations in 36 patients 13,14 . The affected genes code for components of the ETC—Complex I (MT‐ND1, MT‐ND2, MT‐ND4L, and MT‐ND6), Complex IV (MT‐CO3), and the ATP synthase (MT‐ATP8) 14 .…”
Section: Cell Metabolism In Callmentioning
confidence: 99%